Trade policy uncertainty and medical innovation: Evidence from developing nations - Muhammad Nadir Shabbir; Wang Liyong; Muhammad Usman Arshad (Economies, 2022)
This study explores the influence of trade policy uncertainty on medical innovation investment in developing nations from 1980 to 2020, with a focus on the period of COVID-19. We used exogenous and heterogeneous exposure to trade-policy-uncertainty resolutions from developing countries' trade policy adjustments, which reduced tariff hikes on imported goods in a double difference-in-differences method. ARDL with PVAR has been studied for long-run and short-run analyses. The findings revealed that reducing tariff uncertainty boosts innovation beyond patent filings and margin reaction and exports. Long-term impacts of sectoral innovation patterns, governmental changes, and foreign technology entering developing nations have little effect on the findings. This paper also shows a long-term link between medical innovation, trade policy uncertainty, and research-and-development spending. Innovation's negative response to the innovation shock and research and development's positive response corroborates bidirectional and unidirectional causality. This study contributes to medical innovation and policy uncertainty in terms of developing countries and, most importantly, in trends of medical innovation, contemporaneous policy uncertainty given the inflow of foreign technology, and the importance of that technology recent times.
Keywords: D72; F13; F14; O19; O24; O33; P33; 330; uncertainty; trade policy; innovation; patents; developing nations